Chemoselective hydrogenation of cinnamaldehyde over a tailored oxygen-vacancy-rich Pd@ZrO2 catalyst. (15th March 2021) - Patil, Komal N.; Prasad, Divya; Bhanushali, Jayesh T.; Kakade, Bhalchandra; Jadhav, Arvind H.; Nagaraja, Bhari Mallanna
Abstract : Selective hydrogenation of cinnamaldehyde to hydrocinnamaldehyde is captivating due to its industrial relevance. Abstract : Selective hydrogenation of cinnamaldehyde to hydrocinnamaldehyde is captivating due to its industrial relevance. Herein, a two-step synthesis method was adopted to develop oxygen vacancies in Pd@ZrO2 catalysts. The oxygen vacancies were developed in Pd@ZrO2 catalysts during impregnation of Pd which was confirmed by XPS and HR-TEM analyses. The characterization results revealed that there was a synergistic role of oxygen vacancies and nano-sized active Pd metals in Pd@ZrO2 catalysts that assisted in achieving selectivity for hydrocinnamaldehyde which has been discussed in this study. We also studied the effects of different reaction parameters which revealed that 4 wt% Pd loading in a Pd@ZrO2 catalyst provided enough active sites for complete conversion of CAL. Additionally, 100 °C temperature and 10 bar H2 pressure provided enough energy for effective collisions and activation of reactants and catalysts to form the desired product in a reaction time of 9 h. Therefore, a defect-rich 4-Pd@ZrO2 catalyst demonstrated complete CAL conversion with 86% yield towards HCAL which is the best result amongst various Pd@ZrO2 catalysts with different Pd loading investigated for the hydrogenation of cinnamaldehyde. Moreover, a plausible mechanism was proposed to support the chemoselective hydrogenation of cinnamaldehyde over a 4-Pd@ZrO2 catalyst. Along with high catalytic performance, the 4-Pd@ZrO2 catalyst also showed impressive recyclability performance for up to six recycles. Thus, the oxygen-vacancy-rich Pd@ZrO2 can be considered as an efficient catalyst for the chemoselective hydrogenation of cinnamaldehyde.